5 Improving care for patients who have clinical uncertainty of recovery: the lens of acute admissions. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Hayle, C; Jayachandran, A; Kerss, H; Waites, A; Hopper, A; Connolly, V; Hayes, A; Henry, C; Shouls, S; Purewal, G
Abstract : Background: Acute Trusts are an important provider of care for patients who may be in their last months of life; emergency admission may indicate underlying clinical decline. Acute admission processes are not generally designed to manage care for this group. Wirral University Teaching Hospitals NHS Foundation Trust participated in an ECIP-funded End of Life Care Project in 2016/2017 to improve quality of care for this group of patients. Method: An acute physician and a consultant in palliative medicine reviewed 26 deceased patient records using a method designed to uncover clinical system issues and to create a 'common language' between the specialities. This review included focus on patients with clinical uncertainty of recovery. An acute and an elderly care physician carried out 'Plan Do Study Act' tests of change using the AMBER care bundle in the AMU and an elderly care ward for a total of 26 patients. Results: Qualitatively, the review showed that doctors struggled to recognise patients at risk of dying and viewed palliation as an 'all or nothing' approach to care. Tests of change showed an improvement from 75% to 100% recognition of expected deaths; 15% to 42% awareness of what is important to the patient; 53% to 78% preferred place of care recorded; 85% record of what family feels is important. 96% of patients had ceilings of treatment documented. 62% of patients were discharged. Discussion: The numbers are small. Qualitative feedback is initial conversations in AMU set the scene for the whole admission. Feedback was positive however time implications at the 'front door' can present a challenge. Redesign of the process to 'protect' time may be required. Conclusions: This is an important topic. Early recognition of clinical uncertainty, honest conversations can set the scene for the whole admission potentially resulting in improved patient and staff experience.